PERAN KEPALA PESANTREN DALAM MANAJEMEN ORGANISASI DI PONDOK PESANTREN BAHRUL HUDA TEGALDLIMO BANYUWANGI - Muhammad Imam Khaudli; Addullatif Sabudin (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
The goal of this study was to figure out what role the pesantren's head plays in organizational management at Pon-Pes Bahrul Huda. Data was collected through interviews, observation, and documentation as part of the descriptive qualitative research approach. Data reduction, data presentation, and conclusion drafting are the data analysis techniques used. The execution of management activities at Pon-Pes Bahrul Huda goes through numerous stages, including planning, compulsory education program planning, and Islamic boarding school vision and mission. Every month at the beginning of the month, a meeting is held to oversee the operations. The study's conclusion is that at Pon-Pes Bahrul Huda, the leader of the pesantren plays a role in organizational management. Four functions have been implemented by the pesantren's head. Every month at the beginning of the month, a meeting is held to oversee the operations. The conclusion of this study is that the head of the pesantren plays a role in organizational management at Pon-Pes Bahrul Huda. At Pon-Pes Bahrul Huda, the leader of the pesantren has implemented four management functions in order to handle organizational management. Planning, organizing, implementing, and supervising are the four managerial functions.